Negotiating Religious Practices and Islamic Values: Experiences of Pesantren Alumni in Higher Education - Damayanti, Nur Alita; Makrufi, Anisa Dwi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
The transition from a structured pesantren environment to university life requires students to manage their religious commitments under less direct institutional regulation. Previous research has often treated ritual regularity, spirituality, and value internalization as interchangeable, leaving insufficient explanation of how pesantren alumni interpret continuity and change in their religious lives. This study examines reported changes in spiritual and religious experience, the continuation and reinterpretation of Islamic educational values, and the internal and external conditions associated with these processes. A qualitative descriptive design was employed with seven sixth-semester students in an Islamic Religious Education program who had attended a pesantren for at least three years. Data were collected through one semi-structured interview lasting 20–40 minutes with each participant and analyzed using data condensation, data display, and conclusion drawing and verification. The findings show varied rather than uniform trajectories. Five participants reported reduced consistency in one or more practices, including punctual prayer, tahajjud, Qur’anic recitation, memorization, and muraja’ah. These adjustments did not necessarily coincide with the abandonment of Islamic values. Participants described continuing to apply sincerity, discipline, responsibility, moral conduct, consistency, independence, and self-control in academic and social life. Some also reported more reflective interpretations of religious teachings, while others maintained earlier understandings. Personal awareness, self-regulation, peers, family support, campus culture, living arrangements, and academic demands shaped these reported experiences. By distinguishing ritual consistency, value continuity, and reflective religious meaning, the study offers a contextually bounded account of how pesantren alumni negotiate religious commitments in higher education. The findings represent retrospective self-reports and do not establish longitudinal or causal changes in spirituality.